A dual-scale fracture network model for computing hydro-mechanical properties of fractured rock. (October 2021) - Wang, Liang; Lei, Qinghua
Abstract: Fractured geological media often consist of a large number of discontinuities that exist over many different length scales and are associated with scale-dependent hydro-mechanical properties. This raises a great challenge for modelling such hierarchical systems using single scale-based simulations. To overcome this hurdle, in this Note, we propose a dual-scale fracture network model, which explicitly represents the distribution of large-sized fractures while also implicitly respects the contribution of small-sized fractures via an upscaling treatment. We discriminate large and small fractures according to a prescribed length scale (determined via a numerical convergence examination), based on which the domain is discretised into a mesh of grid blocks. A modified crack tensor method is employed to derive the equivalent hydro-mechanical properties of each block containing (entirely or partially) the small-sized fractures. It is shown that the bulk properties of the rock mass can be robustly calculated by this dual-scale model at high accuracy.